In‐Depth Analysis of TiNiPdCu High‐Temperature Shape Memory Alloys Synthesized Using Powder Metallurgy Technique - Abid Hussain; Afzal Khan; M. Imran Khan; Saif Ur Rehman; Fakhre Alam Khan; Asnaf Aziz (Engineering Reports)
ABSTRACT The current research work investigates the effect of copper (Cu) addition on the properties of TiNiPdCu‐based high‐temperature shape memory alloys (HTSMAs) synthesized using powder metallurgy. Shape Memory Alloys (SMAs) with various Cu compositions were prepared and compared to those fabricated using argon arc melting. Microstructural analyses revealed similar characteristics between powder metallurgy and arc melting methods. Scanning Electron Microscope (SEM) observations indicated the presence of second phase precipitates. X‐Ray Diffractometry (XRD) analyses confirmed the presence of martensite phases and second‐phase precipitates. Texture coefficients indicated changes in lattice constants with Cu addition. Transformation temperatures increased by 30% in solution treatment, 31.57% in annealing, and 33.33% in aging, while thermal hysteresis decreased by 31.3% in solution treatment, 24.56% in annealing, and 24.85% in aging. The results suggest that Cu addition influences the microstructure and transformation behavior of TiNiPdCu SMAs, making powder metallurgy a viable method for their fabrication, with potential applications in high‐temperature shape memory applications.